Culture possibility of scheilbeid catfish using formulated feed in natural pond - Razzaque, MA; Mazid, MA; Islam, MN; Mansur, MA (Journal of the Bangladesh Agricultural University, 2010)
A research study was conducted to investigate the culture possibility of fresh water catfish Pangasius pangasius with formulated feed in natural ponds. The stocking density was chosen as 8000 fry/ha with an initial weight of 42.57±2.51 g. The formulated feed contained 45% fishmeal, 30% mustard oil cake, 15% wheat bran and 10% rice bran to supply 40.48% protein in feed. The growth of Pangasius pangasius in terms of net weight gain was found as 266.49g, which was statistically significant (p<0.05). The food conversion ratio (FCR) observed during this research study was high (7.58). There was no variation in the biochemical composition of the fish as a result of such culture technique and experimental conditions. The whole experiment was conducted for a period of 10 months. Production of fish was found to be 2.13 tones/ha using this formulated feed. Keywords: Culture; Pangasius pangasius; Formulated feed; Pond DOI: 10.3329/jbau.v6i2.4837 J. Bangladesh Agril. Univ. 6(2): 375-380, 2008